Dakwah Virtual, Generasi Z dan Moderasi Beragama - Nur Kholis (IQTIDA : Journal of Da'wah and Communication, 2021)
One of the most interesting phenomena to notice is the transition of da'wah from conventional to virtual. The development of information technology has had a significant impact on the social order, especially the world of da'wah. The emergence of various social media da'wah has nourished the development of virtual proselytizing, even more so when dealing with Generation Z. This research intends to reveal the virtual da'wah phenomena on social media that are currently in demand by Generation Z. Descriptive qualitative is used in this research. This research also used library research, as a method of data collection. This research concludes that there are three main subjects in looking at virtual da’wah, generation z, and religious moderation. First, Generation Z has a unique character, different from previous generations. Generation Z can also be called iGeneration or net generation because all its movements cannot be released with gadgets and the internet. Second, Gen Z has a hand in the transition of da'wah in Indonesia, from conventional da'wah to virtual da'wah in the digital space. Third, Gen Z has the characteristics of being an open and tolerant generation. Even so, some research have found that many Gen Z is exposed to intolerant and radical teachings in the jungle of the internet